Structural and luminescence properties of Fe3+ Doped antimony lead borophosphate glass - Leong, Pau Ming; Eeu, Tien Yew; Leow, Ting Qiao; Pang, Xie Guan; Zuhairi Ibrahim,; Rosli Hussin, (Universiti Kebangsaan Malaysia, 2014)
Structural and luminescence properties of borophosphate glasses with different modifier doped with transition metal ions have been investigated in this study. The glass sample from the series of xPb3O4:0.2Sb2O3:0.3B2O3:(0.5-x)P2O5 and ySb2O3:0.2Pb3O4:(0.5-y)B2O3:0.3P2O5 where 0≤ x ≤0.20 mol% and 0 ≤ y ≤ 0.15mol%, respectively, were doped with 0.01 mol% of Fe2O3 system have been prepared using the melt-quenching technique. The structural properties of samples had been studied using fourier transform infrared (FT-IR) spectroscopy. The FT-IR study showed the network structure of the studied glasses based on the B2O3-P2O5 host with the Sb2O3 and Pb2O3 modifiers. The results of FT-IR showed traces of BO3 and BO4 with the introduction of Sb2O3 and Pb2O3 modifiers. With the increasing content of B2O3 which replacing content of P2O5 in the glass network, the intensity of the borate band decreases and shifted to lower frequency. UV-Vis spectroscopy analysed the transition of Fe3+ from ground state to excited state in the ultraviolet spectral region. The photoluminescence of samples were studied using photoluminescence spectroscopy. The result of photoluminescence spectroscopy showed the effect of photoluminescence enhancement by doping Fe3+ as activator.